Making money : life, death, and early modern trade on Africa's Guinea Coast - Kriger, Colleen E. (Africa in world history., 2017)
A new era in world history began when Atlantic maritime trade among Africa, Asia, Europe, and the Americas opened up in the fifteenth century, setting the stage for massive economic and cultural change.